Poned-Based Public Service Innovation in Efforts to Service Pregnant Women at the Wonoasih Health Center, Probolinggo City - Septiandika, Verto; Mustofa, Ahmad; Fitria, Syarla Fian; Wahyu, Fitriana; -Fr, Jalal Ludin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This research was about PONED-based public services in efforts to service pregnant women at the Wonoasih Health Center, Probolinggo City. The background of this research was the insufficient examination of pregnant women at the Wonoasih Health Center, Probolinggo City. So that the innovation developed in service delivery was through PONED services. The research method used was descriptive qualitative method. The results of this study were that the Wonoasih Health Center provides specialized PONED services to deal with cases of obstetric emergencies and neonatal procedures that occur during pregnancy, childbirth, and the postpartum period, and are potentially dangerous for the mother and baby. One of them was outlined in the